PEMBUATAN E-MODULE BERBASIS GUIDED DISCOVERY LEARNING PADA MATERI LARUTAN PENYANGGA - Rima Mayesmy Harahap; Elvinawati; Nurhamidah (University of Bengkulu, 2022)
ABSTRACT This research on making a Guided Discovery Learning (GDL) based chemistry E-module aims to help students understand the buffer solution material more easily and is oriented towards creating meaningful learning. E-module creation using the ADDIE development model. The research was conducted at SMA Negeri 4 Bengkulu City with a research sample of 12 students of class XII MIPA 4 for small-scale trials. The research data were obtained from interviews, material and media validation questionnaires and student response questionnaires. From the research results obtained (1) the feasibility level of the E-module on the material aspect was 93.11% while from the media aspect it was 88.33% so that based on the results of the validation by the E-module validator it was declared very valid, (2) the percentage of E-module achievement increating meaningful learning was 90% with very valid criteria, (3) the percentage of conformity of the E-module component with the cognitive level of Bloom’s taxonomy was 100% with high criteria. and (4) student response to the E-module was 84,16% with very interesting criteris, so it was known that the E-module that has been made interesting and feasible to use because it can make it easier for students to understand learning materials and can create meaningful learning. Keywords: E-module, Guided Discovery Learning, Buffer Solution, ADDIE.